Comparison of rosemary and mefenamic acid capsules on menstrual bleeding and primary dysmenorrhea: A clinical trial - Fahimeh Tahoonian-Golkhatmy; Zahra Abedian; Seyed-Ahmad Emami; Habibollah Esmaily (Wolters Kluwer Medknow Publications, 2019)
Background: Primary dysmenorrhea is the most common complaint of women. Imbalance secretion of prostaglandin from the endometrium during menstruation cycle is effective in primary dysmenorrhea and menstrual bleeding. The aim of this study was to compare rosemary capsule and mefenamic acid on menstrual bleeding and primary dysmenorrhea. Materials and Methods: This randomized double-blinded study was conducted on 82 students with primary dysmenorrhea in the Islamic Azad University of Mashhad in 2016. Participants had moderate dysmenorrhea and normal menstrual bleeding. No intervention was carried out at the two cycles. During the next two cycles, participants were randomly divided into two groups (rosemary and mefenamic acid(. Participants in the intervention group received 250 mg rosemary capsules and the control group received 250 mg mefenamic acid capsules in the first 3 days of menstruation. The visual analogue scale (VAS) was used to determine the severity of pain and Hingham chart to determine the amount of bleeding in menstruation. Independent t-tests, Mann--Whitney were used for statistical analysis. p < 0.05 was considered statistically significant. Results: Pain intensity score standard deviation (SD) before and after intervention for rosemary group were 40.39 (11.41) and 23.57 (12.78) (t41 = 9.90, p < 0.001). For the control group, they were 46.75 (13.32) and 28.29 (17.21) (t39 = 9.10, p < 0.001). Menstrual bleeding score (SD) before and after intervention for rosemary group were 55.21 (21.32) and 46.30 (24.16) (t41 = 2.60, p = 0.01). For the control group, they were 51.05 (23.87) and 43.43 (29.47) (t39 = 2.10, p = 0.01). There was no statistically significant difference between the pain severity and menstrual bleeding score SD in these two groups. Conclusions: Rosemary capsules reduce the menstrual bleeding and primary dysmenorrhea the same as mefenamic acid capsules.